Fatal case of multiple recurrences of endometrial stromal sarcoma after fertility‐sparing management. Issue 1 (27th August 2014) - Morimoto, Atsushi; Tsubamoto, Hiroshi; Inoue, Kayo; Ikeda, Yuuki; Hirota, Seiichi
Abstract Several cases of the uterus being preserved after diagnosis of endometrial stromal sarcoma (ESS) have been reported. Most of these patients were alive and did not experience relapse, but this might have reflected the short follow‐up period, given the indolent recurrence of ESS. We report the first fatal case of ESS 10 years after fertility‐sparing management. A specimen obtained from the last operation showed loss of estrogen receptor status and expression of c‐kit without c‐kit or PDGFR‐α gene mutations.